Thermal properties of AlGaN/GaN high electron mobility transistors on 4H and 6H SiC substrates. Issue 12 (21st August 2014) - Killat, Nicole; Pomeroy, James W.; Jimenez, Jose L.; Kuball, Martin
<x xml:space="preserve">Abstract</x> Micro‐Raman thermography was employed to study the difference in thermal properties of identical, state‐of‐the‐art AlGaN/GaN devices grown onto 4H SiC and 6H SiC substrates. Using temperature profiles in the devices taken laterally across the device surface and vertically through the device structure of multiple devices, a 10% higher peak temperature for AlGaN/GaN transistors on 6H SiC when compared to devices on 4H SiC was found. The comparison of experimental temperature with three‐dimensional finite difference thermal simulations determined a room temperature thermal conductivity of 4.1 W cm−1 K−1 and 4.5 W cm−1 K−1 for devices on the studied 6H and 4H SiC, respectively, as underlying physical reason for this temperature difference, while the thermal boundary resistance between the GaN and the SiC were identical within the experimental error bar for both GaN‐on‐SiC wafers, independent on polytype.